Styling Sagaciousness Oh Great No! - Nechvatal, Joseph (punctum books, 2022)
During the Paris pandemic confinement period of 2020, with the dread of viral death in the air, artist Joseph Nechvatal finished his second book of poetry, titled Styling Sagaciousness: Oh Great No! The mythopoeic mélange of Styling Sagaciousness is intended as a complicated forensic fairy-tale, suitable for Nô theater, which keeps slipping in and out of idiosyncratic narration, a ghostly appearance-disappearance act that turns on the nub of our narcissism concerning our death - that strange, incurable, and deeply irrational affliction we all share. Putting identity aside, Nechvatal's poetry tests the limits of form and stretches the bounds of meaning by recasting our experiences of encountering our self as the sumptuous physicality of total negation. As such, Styling Sagaciousness delivers an airy irrational punch of needed nonsensical negation by tying together insouciant informality with a visceral camp irony: at turns hip and flamboyant and morally outrageous. This seven-part death farce epic poem follows up Nechvatal's sex farce epic poem Destroyer of Naivetés. Nechvatal intends these two books (with complementary cover images of his painting penelOpe in agOny) to be the sum total of his mature poetic output; addressing first Eros, and then, with Styling Sagaciousness, Thanatos.